On stabilization of Poisson integral for equations of Kolmogorov type - Malytska, H.P.; Burtnyak, I.V. (Carpathian Mathematical Publications, 2013)
Stabilization of Poisson integral for Kolmogorov equations is studied. Such equations have three groups of variables with degeneration of parabolicity.